The Influence of Interlocking Labyrinth Seal Cavity Dimension on Leakage - 王琰; 张开林; 王丽娜 (机车电传动)
Taking the labyrinth seal of the transmission gearbox for a certain type of high-power locomotives as researching object, twodimensional structured grid model of the interlocking labyrinth channel was set up by means of software GAMBI. The software Fluent was used in calculating labyrinth seal flow field and leakage flow rate, which were effected by the depth to width ratio and the tooth thickness to clearance ratio. The results showed that: the leakage decreased first and then increased with the increase of the depth to width ratio, the optimum depth to width ratio was about 0.9. Larger the width of cavity, the depth to width ratio effected leakage more obviously; the leakage increased first and then decreased slowly with the increase of the tooth thickness to clearance ratio.